2009
DOI: 10.1108/09615530910930946
|View full text |Cite
|
Sign up to set email alerts
|

Developing laminar mixed convection of nanofluids in an inclined tube with uniform wall heat flux

Abstract: Purpose -The aim is to study the conjugate problem of developing laminar mixed convection flow and heat transfer of water-Al 2 O 3 nanofluid inside an inclined tube submitted to a uniform wall heat flux. Design/methodology/approach -The set of non-linear, coupled and fully elliptic governing equations has been solved using a ''finite-control-volume'' numerical method, the classical power-law scheme for computing heat and momentum fluxes staggered and non uniform grids for spatial discretization of various regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 32 publications
4
16
0
Order By: Relevance
“…In addition, at lower velocities, the effect of natural convection is increased and as a result less pressure drop is obtained. For the tested Ri ranging from 0.1 to 12 which assures having a mixed convection regime, similar trends were achieved by other scientists [6,12].…”
Section: Validation Of the Experimental Facilitysupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, at lower velocities, the effect of natural convection is increased and as a result less pressure drop is obtained. For the tested Ri ranging from 0.1 to 12 which assures having a mixed convection regime, similar trends were achieved by other scientists [6,12].…”
Section: Validation Of the Experimental Facilitysupporting
confidence: 86%
“…Knowledge of the heat transfer characteristics under both conditions is necessary for the design of a heat exchanger. Ben Mansour et al [6,7] studied the conjugate problem of laminar mixed convection flow of Al 2 O 3 /water nanofluid in a uniformly heated inclined tube, both experimentally and numerically. They found that the presence of nanoparticles intensifies the buoyancy-induced secondary flow, especially in the developing region.…”
Section: Introductionmentioning
confidence: 99%
“…Most such studies have treated nanofluids as single-phase fluids with effective thermophysical properties which are obtained from a combination of the corresponding properties of the liquid carrier and the solid particles (Abu-Nada et al, 2008;Akbarinia and Behzadmehr, 2007;Ben Mansour et al, 2009;Maiga et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the capability of nanofluids for the heat transfer enhancement purpose has clearly been established for internal flow configurations -see in particular Pak and Cho [1], Li and Xuan [2], Wen and Ding [3], Yang et al [4], Maïga et al [5,6]. A similar heat transfer enhancement was also observed experimentally for a closed-liquid system destined for cooling of high-powered electronic components, Roy et al [7] and Nguyen et al [8], as well as in cases of free convection (Polidori et al [9]) and laminar mixed convection flow (Ben Mansour et al [10][11][12] and Popa et al [13]). …”
Section: Introductionmentioning
confidence: 58%